Ứng dụng công nghệ số trong dạy học STEM chủ đề “Trí tuệ nhân tạo AI” cho học sinh tiểu học - Phạm Thị Quỳnh Anh, Phạm Thị Quỳnh Anh; Bùi Văn Hồng, Bùi Văn Hồng (Tạp chí Giáo dục, 2026)
The era of Industry 4.0 requires widespread digital transformation in the field of education. The integration of digital technology into teaching has become an inevitable trend to innovate teaching methods and improve training quality (Ministry of Education and Training, 2023). Especially for the topic of STEM education - an interdisciplinary teaching model that integrates Science, Technology, Engineering, and Mathematics - applying digital technology plays an essential role as a powerful supporting tool, helping to realize interdisciplinary educational ideas through experiential and practical approaches. In this article, we propose a STEM teaching organization process integrated with digital technology, with the theme “Artificial Intelligence” (AI) for elementary school students. Through the use of simulation software, simple visual programming tools such as Tinkercad, Scratch, and digital learning activities, the application of digital technology in teaching helps students not only access fundamental concepts of AI but also develop logical thinking, creativity, problem-solving skills, and critical thinking in practical contexts (Tsupros, Kohler & Hallinen, 2009). Additionally, the topic contributes to increasing learning interest, enhancing interaction, and improving knowledge acquisition efficiency among elementary students, while ensuring that educational activities are closely linked to real-life situations.